Risk of colorectal cancer associated with BRCA1 and/or BRCA2 mutation carriers: systematic review and meta‐analysis. Issue 8 (16th April 2020) - Cullinane, C. M.; Creavin, B.; O'Connell, E. P.; Kelly, L.; O'Sullivan, M. J.; Corrigan, M. A.; Redmond, H. P.
Abstract : Background: Carriers of the BRCA1 and/or BRCA2 mutation incur a lifetime risk of up to 85 per cent for breast cancer, and between 20 and 40 per cent for ovarian cancer. Efforts to estimate the lifetime risk of developing colorectal cancer for BRCA mutation carriers have produced conflicting results. Consequently, there are no formal guidelines regarding the need for bowel screening for individuals with BRCA1 and/or BRCA2 mutations. This systematic review and meta‐analysis determined the risk of colorectal cancer associated with BRCA carrier mutations. Methods: The primary outcome was incidence of colorectal cancer in BRCA mutation carriers. Secondary outcomes were the incidence in BRCA1 and BRCA2 carriers, Ashkenazi Jews, and age‐ and sex‐matched cohorts. Results: Eleven studies were included in the review, with an overall population of 14 252 and 4831 colorectal cancers identified. Nine studies were included in the meta‐analysis. There was no increase in colorectal cancer among patients carrying a BRCA mutation (odds ratio 1·03, 95 per cent c.i. 0·80 to 1·32; P  = 0·82). After adjustment for Ashkenazi heritage, and age and sex estimates, there was no increased odds of developing colorectal cancer (with no heterogeneity, I 2  = 0 per cent). Conclusion: BRCA1 and/or BRCA2 mutation carriers are not at a higher risk of colorectal cancer. Abstract : BRCA1 and/or BRCA2 mutation carriers incur a lifetime risk of up to 85 per cent for breast cancer, and between 20 and 40 per cent for ovarian cancer. The aim of this study was to clarify whether an association between BRCA mutation and colorectal cancer risk exists by conducting a systematic review and meta‐analysis of published peer‐reviewed studies. There was no significant increase in the odds of having colorectal cancer in patients carrying a BRCA mutation (odds ratio 1·03, 95 per cent c.i. 0·80 to 1·32; P  = 0·82). No increased risk Abstract : Antecedentes: Las portadoras de la mutación BRCA1 y/o BRCA2 presentan un riesgo a lo largo de la vida de hasta un 85% para presentar un cáncer de mama y entre 20‐40% para el cáncer de ovario. Los esfuerzos para estimar el riesgo de desarrollar cáncer colorrectal ( colorectal cancer, CCR) a lo largo de la vida en portadoras de mutaciones BRCA han dado resultados contradictorios. En consecuencia, no existen pautas formales con respecto a la necesidad de realizar el cribado de CRC en personas portadoras de mutaciones BRCA1 y/o BRCA2. Esta revisión sistemática y metaanálisis analiza el riesgo de CRC asociado en pacientes portadoras de mutaciones BRCA. Métodos: Se incluyeron nueve estudios en el metaanálisis. La población general del estudio fue de 18.839 pacientes, con 4.978 con CRC identificado. La variable principal fue la incidencia de cáncer colorrectal en portadoras de mutaciones BRCA. Las variables secundarias incluyeron el análisis de la incidencia de subgrupos en BRCA 1, BRCA 2, etnia judía Ashkenazi y cohortes emparejadas por edad y sexo. Resultados: No hubo un aumento de CRC en pacientes con una mutación BRCA (razón de oportunidades, odds ratio, OR 1, 03; i.c. del 95% 0, 80‐1, 32; P = 0, 82). Cuando se ajustó de acuerdo con la ascendencia Ashkenazi y las estimaciones de edad y sexo, no hubo mayores probabilidades de desarrollar cáncer colorrectal (sin heterogeneidad en los estudios (I 2 = 0)). Conclusión: Este metaanálisis concluye que el riesgo de cáncer colorrectal no fue significativamente mayor en las portadoras de mutaciones BRCA1 y/o BRCA2. Sin embargo, se requiere más evidencia antes de no recomendar la colonoscopia de cribado a las portadoras de la mutación BRCA1/2. Las pruebas de inmunoquímica fecal pueden ser una alternativa apropiada en esta población.